(untitled) (Research, Society and Development, 2024)
Oral squamous cell papilloma is a localized exophytic proliferation with a wart-like or cauliflower-like appearance, usually asymptomatic and slow growing. It is the most common benign lesion of the oral epithelium. It has no gender predilection and commonly occurs between the third and fifth decades of life, although it may also occur during childhood. It is often found on the palate, tongue, lips or gums. Treatment usually involves surgery to remove the lesion completely, however, there are other treatment options. The risk of the lesion becoming malignant is low and the lesion does not usually recur. The focus of this article is to analyze the main aspects of oral squamous papilloma such as clinical and histopathologic features, diagnosis, treatment and recurrence. A clinical case of an oral squamous cell papilloma located in the interincisive papilla will also be included.